Transitional democracy, diversity and education from the Croatian perspective - Spajić-Vrkaš, Vedrana (2013)
When compared to the developed democracies, transitional countries appear as the highly fragile systems. The latter are, in the words of Roland Inglehart (2003), formal but ineffective democracies in a sense that they guarantee their citizens a wide array of rights and freedoms but deprive them of proper resources to exert their rights effectively. One of the essential resources is education providing that it aims at empowering the student as the citizen who is able to balance successfully his or her primordial and instrumental identities by relying on shared democratic values and principles. The devaluation of education as a means of upholding transition to democracy has been a constant drawback of educational reforms in Croatia since its independence in 1991. The country was established by adopting the democratic constitution which defines Croatia in terms of, in the one hand, a nation-state following the ethnic model (Smith 1991) and, in the other hand, a democratic state which guarantees equal rights and freedoms to its citizens. As the proclamation of independence led to the war through which Croatia had to defend its territory, the quest for national renewal and homogenization became the dominant and all-encompassing transitional, albeit political, discourse. The consequence was that transition to democracy was seen more as an outcome of the institutionalization of Croatocentrism than of the empowered and emancipated citizens. In fact, the very concept of the citizen was problematic. It was introduced as a part of the new institutional set-up ; it had no roots in the political culture of the people and its relationship to the constitutional rights and freedoms of the individual remained vague. The citizen’s role was primarily interpreted in terms of his/her duties towards the new nation state and not in terms of his/her active participation in decision making for the purpose of better protecting his/her constitutional rights and freedoms, which is the reason why there was and still is a lot of misunderstanding when the issue of “makind the citizen” (Callan 1997) through school is considered. On the other hand, the membership in the international and European organisations required Croatia to fully promote the principles of human rights, equality and diversity through, among other means, education. As the pressure from these organisations and an emerging civil society were, throughout the 1990s, mainly focused on the protection of minority rights, the response of the Croatian government was twofold. The government, in the one hand, established educational provisions for minority students in line with bilateral agreements and, in the other hand, proclaiming the principles of human rights and active citizenship as the target values and the basis for educational changes. The latter appeared as a political catchphrase that did not challenge the system. School curricula were heavily dependent on traditional academic disciplines and oriented towards either the students’ academic knowledge or their vocational skills. Educational theory was still focused on students as intellectual, social, moral and aesthetic beings but forgot to see them as political subjects who negotiate and re/de/construct their reality. As some recent studies demonstrate, the outcomes of such mis-match are damaging. The students’ understanding of the role of the citizen and the government, as well as of the key principles of democracy, including the rights, equality, diversity and non-discrimination, are less than moderate. The data on their civic and political culture portray them as passive and self-centred young individuals who have little trust in democratic institutions, political actors and the civil society. Very few are engaged in the activities that benefit their local communities. They also appear to be socially distanced from all neighbouring national and religious groups to the level of “us” and “them” dichotomy. Moreover, many are undecided about the value of the European integration and fear that Croatian accession to the European Union will not lead to significant social, political and economic improvement but imperil national identity, sovereignty and wealth.
ENG